Dual melanocortin‐4 receptor and GLP‐1 receptor agonism amplifies metabolic benefits in diet‐induced obese mice. Issue 3 (4th February 2015) - Clemmensen, Christoffer; Finan, Brian; Fischer, Katrin; Tom, Robby Zachariah; Legutko, Beata; Sehrer, Laura; Heine, Daniela; Grassl, Niklas; Meyer, Carola W; Henderson, Bart; Hofmann, Susanna M; Tschöp, Matthias H; et al.
Abstract We assessed the efficacy of simultaneous agonism at the glucagon‐like peptide‐1 receptor (GLP‐1R) and the melanocortin‐4 receptor (MC4R) for the treatment of obesity and diabetes in rodents. Diet‐induced obese (DIO) mice were chronically treated with either the long‐acting GLP‐1R agonist liraglutide, the MC4R agonist RM‐493 or a combination of RM‐493 and liraglutide. Co‐treatment of DIO mice with RM‐493 and liraglutide improves body weight loss and enhances glycemic control and cholesterol metabolism beyond what can be achieved with either mono‐therapy. The superior metabolic efficacy of this combination therapy is attributed to the anorectic and glycemic actions of both drugs, along with the ability of RM‐493 to increase energy expenditure. Interestingly, compared to mice treated with liraglutide alone, hypothalamic Glp‐1r expression was higher in mice treated with the combination therapy after both acute and chronic treatment. Further, RM‐493 enhanced hypothalamic Mc4r expression. Hence, co‐dosing with MC4R and GLP‐1R agonists increases expression of each receptor, indicative of minimized receptor desensitization. Together, these findings suggest potential opportunities for employing combination treatments that comprise parallel MC4R and GLP‐1R agonism for the treatment of obesity and diabetes.